EFFECT OF CONSUMING RED SPINACH (AMARANTHUS TRICOLOR L) EXTRACT ON HEMOGLOBIN LEVEL IN POSTPARTUM MOTHERS - Resty Himma Muliani (Belitung Raya Foundation, 2017)
Background: Postpartum mothers are susceptible to anemia, due to loss of blood count during labor. Postpartum anemia causes uterine subinvolution which causes postpartum hemorrhage, facilitates puerperium infection, decreases breastfeeding and easy mamae infection. One alternative to prevent anemia in postpartum is to consume vegetables with high iron one red spinach. Red spinach is one of the non-heme iron sources needed to synthesize hemoglobin. Objective: To determine the effect of red spinach in increasing the levels of hemoglobin in postpastum mothers. Methods: This was a quasy experiment with pretest posttest with control group design in October-December 2017 at the Community Health Center of PONED Tarub, Tegal regency. Thirty postpartum mothers were included using purposive sampling, which 15 assigned in each group. Blood sampling and examination were performed in each respondent. Paired and Independent t-test were done for data analysis. Results: The results of the 14-day intervention of given red spinach extract showed that there was a significant increase of hemoglobin level (1.25 g / dL) with p-value 0.047. Conclusion: There is a significant effect of consuming red spinach extract (amaranthus tricolor L.) on the increase of hemoglobin level in postpartum mother. It is recommended that midwives could apply this intervention and cooperate with agriculture and food processing in order to produce red spinach extract that increases hemoglobin, hematocrit and erythrocytes levels.